2017
DOI: 10.1126/sciimmunol.aam6346
|View full text |Cite
|
Sign up to set email alerts
|

Resident memory T cells in the skin mediate durable immunity to melanoma

Abstract: Tissue-resident memory T cells (TRM cells) have been widely characterized in infectious disease settings; however, their role in mediating immunity to cancer remains unknown. Here we report that skin-resident memory T cell responses to melanoma are generated naturally as a result of autoimmune vitiligo. Melanoma antigen-specific TRM cells resided predominantly in melanocyte-depleted hair follicles and were maintained without recirculation or replenishment from the lymphoid compartment. These cells expressed CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
209
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(219 citation statements)
references
References 30 publications
10
209
0
Order By: Relevance
“…Importantly, the density of T RM cells within the tumor environment has been shown to predict for improved survival in a number of cancer types, including advanced‐stage melanoma . In line with this, recent reports have shown that T RM cells afford potent antitumor immunity in mouse models . Furthermore, we have recently demonstrated that T RM cells can promote cancer‐immune equilibrium in mouse skin by keeping dispersed melanoma cells dormant over extended periods of time .…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…Importantly, the density of T RM cells within the tumor environment has been shown to predict for improved survival in a number of cancer types, including advanced‐stage melanoma . In line with this, recent reports have shown that T RM cells afford potent antitumor immunity in mouse models . Furthermore, we have recently demonstrated that T RM cells can promote cancer‐immune equilibrium in mouse skin by keeping dispersed melanoma cells dormant over extended periods of time .…”
Section: Introductionsupporting
confidence: 59%
“…15 In line with this, recent reports have shown that T RM cells afford potent antitumor immunity in mouse models. 10,13,[16][17][18] Furthermore, we have recently demonstrated that T RM cells can promote cancer-immune equilibrium in mouse skin by keeping dispersed melanoma cells dormant over extended periods of time. 19 Whether T RM cells have a similar function in maintaining tumor dormancy in humans, however, remains to be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…T RM expressing CD49a were also observed both in the dermis and epidermis of vitiligo lesional skin and were characterized by production of IFNγ, perforin and granzyme B, notably when T RM cells were cultured in the presence of IL‐15, a cytokine that has been shown to be involved in T RM differentiation and maintenance. In line with the involvement of T RM in vitiligo, melanoma‐associated vitiligo supports T RM that can provide anti‐tumor immunity in vivo …”
Section: Vitiligo: a Skin Memory Diseasesupporting
confidence: 52%
“…8 Another report revealed that CD49a+ CD103+ CD8+ T RM cells in human vitiligo vulgaris were poised for cytotoxic functions. In particular, CD49a+ CD103+ CD8+ T RM cells were present only in perilesional skin.…”
Section: Identification Of Cd49a+ Cd8+ Resident Memory T Cells In Vitmentioning
confidence: 99%